Process-Based vs. Product-Based Approaches in Teaching Academic Writing: A Comparative Study - Asrifan, Andi; Luís Miguel Oliveira de Barros Cardoso; K. J. Vargheese; Raveenthiran Vivekanantharasa (International Journal of Language Pedagogy, 2025)
Academic writing is essential in higher education, especially for English as a Foreign Language (EFL) learners who need to adhere to academic and publication standards. This research was carried out in the English Education Department of a public university in Indonesia, involving 40 undergraduate students aged 19 to 22 with intermediate English competence. Employing a mixed-methods quasi-experimental design, two intact classrooms were allocated distinct instructional methodologies during an eight-week period: one engaged in process-based teaching, while the other participated in product-based teaching. Quantitative analysis utilizing paired and independent sample t-tests indicated that the process-based group exhibited substantially larger improvement (M = 78.65, SD = 4.88) compared to the product-based group (M = 73.40, SD = 5.12), t(38) = 3.17, p < 0.01. The process-oriented approach also resulted in enhanced coherence, vocabulary, and structure. Qualitative findings from student interviews and reflections corroborated these outcomes, indicating enhanced engagement, motivation, and confidence among process-oriented learners. The results demonstrate that recursive writing techniques and iterative feedback significantly promote enduring writing advancement. The study advocates for the incorporation of process- and product-oriented components to improve EFL academic writing instruction in Indonesian higher education.